Relationship between locked modes and thermal quenches in DIII-D. (28th March 2018) - Sweeney, R.; Choi, W.; Austin, M.; Brookman, M.; Izzo, V.; Knolker, M.; La Haye, R.J.; Leonard, A.; Strait, E.; Volpe, F.A.
Abstract: Locked modes are known to be one of the major causes of disruptions, but the physical mechanisms by which locking leads to disruptions are not well understood. Here we analyze the evolution of the temperature profile in the presence of multiple coexisting locked modes during partial and full thermal quenches. Partial quenches are often observed to be an initial, distinct stage in the full thermal quench. Near the onset of partial quenches, locked island O-points are observed to align with each other on the midplane, and their widths are sufficient to overlap each other, as indicated by the Chirikov parameter. Energy conservation analysis of one partial thermal quench shows that the energy lost is both radiated in the divertor region, and conducted or convected to the divertor. Nonlinear resistive magnetohydrodynamic simulations support the interpretation of stochastic fields causing a partial axisymmetric collapse, though the simulated temperature profile exhibits less degradation than the experimental profiles. In discharges with minimum values of the safety factor above  ̃1.2, locked modes are observed to self-stabilize by inducing, possibly via double tearing modes, a minor disruption that removes their neoclassical drive. These high q min discharges often exhibit relatively low ratios of the plasma internal inductance to the safety factor at 95% of the poloidal flux, which might imply classical stability, in agreement with the decay of the mode when the neoclassical drive is removed.